Bestuursvlak se verband met fisieke aktiwiteit, lewenstyl en gesondheidstatus by vroulike bestuurslui - Koekemoer, Marisa (North-West University (South Africa), 2002)
The relationship of managerial level with physical activity, lifestyle and health status among female managers. Due to technological advances and mechanization, physical activities m today's occupations have been reduced to the minimum. The consequences are a variety of degenerative conditions that can contribute to hypertension, stroke, heart disease and premature aging. The productivity of employees is often a direct result of their general health status and research has shown that participation in training programs based on scientific principals can improve work production, stress management, vitality and quality of life in general. The influence of managerial level is still regarded as a problem were participation in physical activity, lifestyle and health status is concerned. The aim of this study was firstly to investigate the relation of managerial level with life style, physical activity and health status. Secondly, the influence of physical activity and lifestyle on the possible relation between managerial level and health status was determined. The subjects of this study were drawn from the SANGALA-data from companies all over South Africa. The group consisted of 307 female executives with an average age of 38.30 ± 9.08-year. The data were collected by means of questionnaires. Participation in physical activity was determined with the Physical Activity Index (Sharkey, 1984:5). Lifestyle was determined with the Belloc and Breslow (1972:46-64) questionnaire and health status was measured by the Seriousness of Illness Rating Scale (Wyler et al., 1968:363-374). To indicate the difference between the variables, t-tests, two-way analyses of variants and Tuckey post hoc comparisons were used. A step wise multiple regression analyses was used to determine the contribution of physical activity, lifestyle, type of occupation, time in occupation, level of academic qualification, age and maintenance of consistent body weight to the variants of health status. No significant (p ~ 0.05) differences were found during the first analyses of managerial level with physical activity, lifestyle and health status. In general the inclination were found that health status are influenced by lifestyle. Sufficient sleep and maintaining constant body mass were the primary contributors towards the variants of health status in the stepwise multiple regression analyses that was performed. Managerial level made no contribution towards the variants of health status in the stepwise multiple regression analyses.
MSc (Biokinetika), North-West University, Potchefstroom Campus
Keywords: Physical activity; Lifestyle; Health; Manager; Female